Repress, Occupy, or Instruct? An Action-Research Study with Justice-Involved Youth in Brazil - Francisco, Julio Cesar (Critical Education, 2026)
This study aims to present, analyze, and discuss an action-research educational experience conducted in a detention center of the Juvenile Justice System in northeastern Brazil. Methodologically, the research was grounded in bibliographic, documentary, and field approaches, using the following research procedures: I. participant observations to closely examine the educational practices developed by educators (teachers and social educators) with male adolescents aged 12 to 17 years; II. establishment of agreements, dialogues, observations, collaborative actions, conflict mediations, and propositions to guide pedagogical activities in the socio-educational unit; III. preparation of a field diary to support the construction of a record of experiences; IV. production of pedagogical resources from the educational practices analyzed and experienced, employing theoretical tools of socialist pedagogical approaches. The research findings identified objectives, content, values, and methods that are aligned with three foundational pedagogical approaches: the Pedagogy of “learning to learn,” Competence Pedagogy, and Repressive Pedagogy. These approaches are eclectically combined in educational practices, proving to be minimally preventive and lacking in deliberate pedagogical character.